Function and mechanism of mesenchymal stem cells in the healing of diabetic foot wounds - Yu, Xiaoping; Liu, Pan; Li, Zheng; Zhang, Zhengdong (Frontiers in Endocrinology, 2023)
Diabetes has become a global public health problem. Diabetic foot is one of the most severe complications of diabetes, which often places a heavy economic burden on patients and seriously affects their quality of life. The current conventional treatment for the diabetic foot can only relieve the symptoms or delay the progression of the disease but cannot repair damaged blood vessels and nerves. An increasing number of studies have shown that mesenchymal stem cells (MSCs) can promote angiogenesis and re-epithelialization, participate in immune regulation, reduce inflammation, and finally repair diabetic foot ulcer (DFU), rendering it an effective means of treating diabetic foot disease. Currently, stem cells used in the treatment of diabetic foot are divided into two categories: autologous and allogeneic. They are mainly derived from the bone marrow, umbilical cord, adipose tissue, and placenta. MSCs from different sources have similar characteristics and subtle differences. Mastering their features to better select and use MSCs is the premise of improving the therapeutic effect of DFU. This article reviews the types and characteristics of MSCs and their molecular mechanisms and functions in treating DFU to provide innovative ideas for using MSCs to treat diabetic foot and promote wound healing.